(untitled) (Eurasian Journal of Ecology, 2020)
The article presents the results of a study of microorganisms capable of isolating target metabolites as candidate objects for the development of a microbiological method of increasing oil recovery of produced formations. The purpose of the study is the screening of microorganisms with oil-diluting and oildisplacing properties isolated from extreme conditions, i.e., developed oil layers. Microorganisms living in oil reservoirs have great biotechnological potential, producing such oil-diluting and oil-displacing metabolites as: organic acids, biosurfactants, solvents, gases. As a result of studies, it was found that of the 15 studied strains of pseudomonas, 6 strains of Pseudomonas aeruginosa (T1, T4, T5, T6, D1, D3) are active acid-forming agents on a minimal medium with the addition of molasses; The ability to active gas producers was revealed in 8 strains of P. aeruginosa (T1, T3, T4, D1, D2, D6, D8, D9); it was shown that the maximum oil emulsification index was 50.4-65% in 7 strains of P.aeruginosa – T5, D1, D2, D3, D7, D8 D9; The ability to active gas producers was revealed in 8 strains of P. aeruginosa (T1, T3, T4, D1, D2, D6, D8, D9). As a result of studying microorganisms with oil-diluting and oil-displacing properties, 5 strains of P.aeruginosa T1, T4, T5, D1, D3, were selected as promising microorganisms for the development of microbial enhanced oil recovery of developed oil layers. Key words: microorganisms, enhanced oil recovery, emulsification index, production of gas, production of acid.